Otimização descentralizada coordenada aliada a estratégias de controle plantwide para o controle de processos químicos - Cardoso, Anamaria de Oliveira (2016)
Chemical plants are increasingly complex and integrated with recycle streams promoting energy integration and increasing process yield. This results in a complex dynamic behavior which can interfer in control systems design. Decentralized control systems are an alternative although this methodologie is not always e ective once that interactions between process units are not considered. In this work, decentralized coordinated optimization with severous methods of coordination is applied to a reactor- ash systems and Williams-Otto plant, getting satisfatory results for these chemical plants. Then, we develop a control system to complex chemical plants that are decomposed in subsystems, combine decentralized coordinated optimization with strategies of plantwide control theory to ensure that processes operate in conditions comply with global and local demands, minimizing the e ect of disturbances in the system and avoiding snowball e ect, characteristics of this type of systems since both methodologies consider the interconnections of the systems. The methodology is applied to design of control systems to Williams-Otto plant, because of complexity of its optimization problem and high f interaction between its process units. The result is a control systems of complex chemical plants with high performance and e ciency, with smooth actions in face of fast disturbances and minimizing their e ects along the plants. Futhermore, there is the importance of applying plantwide control theory in the proposed system, even if decentralized coordinate optimization is used that, alone, does not guarantee the performance and e ectiveness of the designed system.